Evaluation of Prevalence and Antimicrobial Resistance of Salmonella spp Isolated from Chicken Eggs Sold in Ilorin, Nigeria - , Adesina Olusegun Michael; , Opasola Olaniyi Afolabi; , Apata David Friday; , Alli Saliu (Archives of Current Research International, 2018)
Aims: Salmonella is zoonotic bacteria which causes serious economic loss in poultry production and infections in human population. The use of antibiotics for prevention and treatment of diseases has become commonplace in intensive Poultry farming. However, there is a growing concern regarding the development of drug-resistant bacteria. This study was conducted to evaluate the prevalence and antimicrobial resistance of Salmonella spp isolated from eggs sold for human consumption in Ilorin, Nigeria. Study Design: A randomized design was used to collect 480 eggs from 6 collection points (5 poultry farms and 1 market). Ten samples were collected per week from each point. Descriptive statistics was used to analyse the data Place and Duration of Study: Poultry farms and a market in Ilorin, Nigeria were randomly sampled for eggs over 8 weeks between December 2015 and January 2016. Methodology: Egg samples were collected to avoid cross contamination using sterile bags to transport the eggs from the collection points weekly to the Agricultural Laboratory, Kwara State University. The eggs were stored under sterile conditions at 40C until analysed. Standardized microbiological methods were used to isolate Salmonella spp. and identify the serotypes. Disc diffusion technique was used to carry out antimicrobial sensitivity test. Descriptive statistics was utilized in data analysis. Results: An average Salmonella prevalence of 67% was discovered with a multi-drug resistance to all the antimicrobials used except gentamicin. There were 40%, 60%, 80% and 100% resistance to Ceftriaxone, Ofloxacin, Cloxacillin and Cefuroxime respectively. Also Salmonella enteriditis which is important in human health was the most prevalent serotype (47%) in chicken eggs. Conclusion: The prevalence of Salmonella isolated from chicken eggs sold in Ilorin metropolis was very high and multi-drug resistance found along this important human food chain require urgent regulation on the use of antibiotics in poultry.